Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.4 - Multiplying Polynomials - Exercise Set - Page 289: 48



Work Step by Step

$(x-1)^{4} =( (x-1)^{2}) ^{2}$ Using the formula $(a-b)^{2}= a^{2}-2ab+b^{2}$ $ (x-1)^{2} = (x^{2}-2x+1)$ $=(x^{2}-2x+1)^{2}$ $=(x^{2}-2x+1)(x^{2}-2x+1)$ $=x^{4}-2x^{3}+x^{2}-2x^{3}+4x^{2}-2x+x^{2}-2x+1$ Combine like terms. $=x^{4}-2x^{3}-2x^{3}+x^{2}+4x^{2}+x^{2}-2x-2x+1$ $=x^{4}-4x^{3}+6x^{2}-4x+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.